The Quebec Diabetes Empowerment Group Program: Program Description and Considerations Regarding Feasibility and Acceptability of Implementation in Primary Health Care Settings - Hersson-Edery, Fanny; Reoch, Jennifer; Gagnon, Justin (Frontiers in Nutrition, 2021)
Introduction Diabetes is a highly prevalent chronic disease that frequently coexists with other medical conditions and implies a high burden for patients and the healthcare system. Clinicians currently are challenged to provide effective interventions that are both multidisciplinary and empower patient self-care. The Diabetes Empowerment Group Program (DEGP) was developed with the aims of fostering patient engagement in diabetes self-care through the lens of empowerment and to support the empowerment of patients with diabetes by providing multidisciplinary group-based care. This research's objectives were to: 1) develop a comprehensive description of the DEGP for potential adopters, and 2) explore the factors influencing the feasibility and acceptability of implementing it in other healthcare settings in Montreal. Methods A qualitative descriptive study was conducted, following a participatory approach. Data were obtained from: 1) semi-structured interviews with 14 patients who participated in the pilot program; 2) from semi-structured group interviews with patient partners, healthcare professionals, and other stakeholders from 4 Montreal family medicine groups and 3) discussions among the participatory research team during various knowledge translation activities. Inductive content analysis of the data was performed. Results The DEGP identified seven key elements: medical visit, continuity of care, group-based dynamics, multi-disciplinarity, clinician facilitation, patient-centered agenda, and a theoretical framework of empowerment. The content and organization of the group visits were conceived to address each of these four domains. The empowerment framework comprises four domains of self-care: emotional (attitude), cognitive (knowledge), behavioral (skills), and relational (relatedness). Factors impacting the feasibility and acceptability of implementing the DEGP in other primary care settings were identified. Discussion The DEGP fits within the discourse around the need for more patient-centered programs for people living with diabetes, following a more comprehensive empowerment model. This research could facilitate the development or adaptation of similar programs in other settings.